2018
DOI: 10.9775/kvfd.2018.20843
|View full text |Cite
|
Sign up to set email alerts
|

Sığır Serum Albumini İlave Edilmiş Lesitin Bazlı Sulandırıcı İle Sulandırılan Koç Spermasının Dondurma-Çözdürme Sonrası Uzun Süreli İnkübasyon Direnci

Abstract: Long term incubation resilience of post-thaw ram semen diluted with lecithin-based extender supplemented with bovine serum albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It has been preferred in many experiments related to in vitro embryo production of different species and successful results have been obtained [26][27][28] . Moreover, it has been reported by researchers that BSA has beneficial effects on sperm motility and viability in many experiments [10,15,16] . Many studies have supported that BSAsupplemented extenders reduce contact between buck seminal plasma proteins and seminal plasma components like spermatozoa membrane [28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been preferred in many experiments related to in vitro embryo production of different species and successful results have been obtained [26][27][28] . Moreover, it has been reported by researchers that BSA has beneficial effects on sperm motility and viability in many experiments [10,15,16] . Many studies have supported that BSAsupplemented extenders reduce contact between buck seminal plasma proteins and seminal plasma components like spermatozoa membrane [28] .…”
Section: Discussionmentioning
confidence: 99%
“…The BSA is a protein molecule with a large structure which is available in reproductive system fluids. Furthermore, in many research, it has been reported that BSA increases the viability and motility of spermatozoa after cryopreservation [16] . This study was conducted to investigate the usability of Trisbased semen extenders supported by BSA instead of egg yolk as a cryoprotectant in the cooling of buck semen.…”
Section: Introductionmentioning
confidence: 99%